Microwave-assisted extraction of pectin from jackfruit rinds using different power levels - Koh, Pei Chen; Leong, Chia Ming; Mohd Adzahan, Noranizan (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2014)
Pectin is a heterogeneous branched polysaccharide with complex structure. Microwave-assisted extraction (MAE) is more efficient in extracting pectin compared to conventional method. The objective of this study was to compare the efficiency of microwave-assisted pectin extraction against conventional extraction method. This study was also to investigate the effect of power level on yield and quality of extracted pectin from jackfruit rinds. Water-based extraction method was performed with the extraction duration for conventional extraction and MAE were 1 h and 10 min, respectively. The temperature of conventional extraction was set at 90°C and the power levels of MAE were 450 W, 600 W and 800 W. High yield of pectin was obtained from conventional extraction (14.59%) and MAE (16.72-17.63%). All quality characteristics determined were found to be insignificant different for pectin extracted from both conventional extraction and MAE except moisture and ash content. Increase in microwave power did not affect yield and quality characteristics of pectin from jackfruit rinds significantly. In conclusion, MAE requires shorter time than conventional extraction in extracting comparable amount and quality of pectin from jackfruit rinds. Microwave-assisted extraction at 450 W was the most effective and economic extraction condition among the different power levels tested.